CEREBROSPINAL FLUID EVALUATION AS A DIAGNOSIS AND PROGNOSIS TOOL: A BIBLIOMETRIC ANALYSIS OF THE 100 MOST CITED ARTICLES - Figueiredo Filho, Luiz Carlos; Aranha, Maria Fernanda de Almeida Cavalcante; Cabeça, Rafael Augusto Silva; Massoud, Ricardo Ormanes; Cohen, Sarah Brazão; Fernandes, Luanna de Melo Pereira; de Oliveira, Rita de Cássia Silva; Cohen, Patrícia Brazão (Arquivos de Ciências da Saúde da UNIPAR, 2023)
Introduction: Cerebrospinal fluid (CSF) analysis is critical in the diagnosis, prognosis, and treatment of a wide range of diseases, including multiple sclerosis, encephalitis, meningitis, brain tumors, Creutzfeldt-Jakob disease, Alzheimer's disease, and other neurodegenerative conditions. Objective: Bibliometric analysis of the 100 most cited articles to obtain deeper insights into the status of research in this sector, in order to provide support for evidence-based medicine (EBM). Methodology: The main collection of the Web of Science was used to collect relevant studies on the topic, and the VOSviewer software was employed to build bibliometric networks. The examination did not include materials from editorials, books, patents, or research with unspecified designs. The articles chosen are in the time range from 1991 to 2020. Results: It was noted that most of the articles were human observational studies focusing on the diagnosis of neurodegenerative diseases, specifically Alzheimer's, which were published in neurology and/or Alzheimer's-related journals, mainly in the United States of America. We discovered forward-looking research hotspots and trends in this domain, which can serve as an important guide to neurological research, generating subsidies for medical decision-making. Conclusion: The number of primary articles on the subject points to the need for further future research on CSF associated, mainly, with other neurodegenerative diseases, in addition to Alzheimer's, sustaining the diagnostic efficacy and EBM.